A suitable preparation of N-sulfonyl-1,2,3,4-tetrahydroisoquinolines and their ring homologs with a reusable Preyssler heteropolyacid as catalyst - Romanelli, Gustavo Pablo (2010)
The preparation of N-sulfonyl-1,2,3,4-tetrahydroisoquinolines, N-sulfonyl-2,3,4,5-tetrahydro-1H-2-benzazepines and N-sulfonyl-1,2,3,4,5,6-hexahydrobenzazocine was catalyzed by a Preyssler heteropolyacid, H₁₄[NaP₅W₃₀O₁₁₀], (PA), supported on silica (PASiO₂40) with excellent yields by means of the Pictet–Spengler reaction of N-aralkylsulfonamides with s-trioxane. The reactions proceed with 0.5 mol% of silica-supported catalyst in toluene at 70°C. The catalyst can be recycled without appreciable loss of the catalytic activity.